2004
DOI: 10.1029/2004gl020558
|View full text |Cite
|
Sign up to set email alerts
|

Strato‐mesospheric measurements of carbon monoxide with the Odin Sub‐Millimetre Radiometer: Retrieval and first results

Abstract: The Sub‐Millimetre Radiometer (SMR) aboard the Odin satellite has been measuring vertical profiles of atmospheric trace gases since August 2001. We present the inversion methodology developed for CO measurements and the first retrieval results. CO can be retrieved from a single scan measurement throughout the middle atmosphere, with a typical resolution of ∼3 km and a relative error of ∼10% to ∼25%. Retrieval results are evaluated through comparison with data from the Whole Atmosphere Community Climate Model (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 17 publications
7
53
2
Order By: Relevance
“…The 0.1 ppmv contour in CMAM, SMR, and MLS data descends from about 0.5 hPa (∼53 km) in April to about 7 hPa (∼35 km) in July, which corresponds to a descent rate of about 6 km per month. A strong CO meridional gradient in the winter polar region and associated downward transport have been reported in observations by ISAMS (Allen et al, 2000), SMR (Dupuy et al, 2004) and MLS (Pumphrey et al, 2007). The ISAMS observations showed a similar descent rate in the Antarctic upper stratosphere and lower mesosphere from late April to late July ( Fig.…”
Section: Co Comparisonssupporting
confidence: 75%
See 1 more Smart Citation
“…The 0.1 ppmv contour in CMAM, SMR, and MLS data descends from about 0.5 hPa (∼53 km) in April to about 7 hPa (∼35 km) in July, which corresponds to a descent rate of about 6 km per month. A strong CO meridional gradient in the winter polar region and associated downward transport have been reported in observations by ISAMS (Allen et al, 2000), SMR (Dupuy et al, 2004) and MLS (Pumphrey et al, 2007). The ISAMS observations showed a similar descent rate in the Antarctic upper stratosphere and lower mesosphere from late April to late July ( Fig.…”
Section: Co Comparisonssupporting
confidence: 75%
“…CO is retrieved from the 576.6 GHz band between ∼18-100 km with an altitude resolution of about 3 km. The retrieval methodology for CO is described by Dupuy et al (2004). N 2 O is retrieved from a line at 502.3 GHz in the altitude range 13-50 km with a vertical resolution of 1.5-2 km .…”
mentioning
confidence: 99%
“…estimated at better than 25 ppbv in the stratosphere increasing up to 1-2 ppmv at ∼80 km (Barret et al, 2006). The SMR CO measurements and data analysis methodology were described in detail by Dupuy et al (2004). Early qualitative comparisons with ACE-FTS were published by Jin et al (2005), whilst a detailed comparison of SMR/Odin with Aura/MLS can be found in Barret et al (2006).…”
Section: Smr/odinmentioning
confidence: 99%
“…López-Valverde et al, 1993;Dupuy et al, 2004;Filipiak et al, 2005;Clerbaux et al, 2008;Funke et al, 2009). In contrast to ground-based measurements, which provide a high temporal and horizontal resolution at the measurement location, the advantage of satellite observations is good spatial coverage, and therefore a global view on CO abundances.…”
Section: Introductionmentioning
confidence: 99%